Building communities in times of crisis - Impacts of the COVID-19 pandemic on the work of transition intermediaries in the energy sector. (May 2021) - Busch, Henner; Hansen, Teis
Abstract: The ongoing COVID-19 pandemic affects people worldwide. The policies in response to the virus range from closure of national borders to curfews for entire metropolises, like Paris. While we can expect severe impacts on the world economy, the consequences of the pandemic for local sustainability transitions are entirely unclear. In this exploratory study, we investigate how the current situation affects the work of transition intermediaries in the energy sector. More concretely, we aim to analyse the impact of COVID-19 policies on community energy projects and the subsequent change of work practices of intermediaries in this situation. Our data consists of qualitative data we collected between January and October 2020. Our results show that transition intermediaries are affected in different ways. Most notably, the work on networking suffers during these times of crisis. We found that intermediaries are particularly challenged in their ability to build trust. This particularly affects new and complex community energy projects and intermediation activities needed for systemic change. We found that established projects with a strong trust base are least affected by these limitations. Intermediaries dependent on private funding face much bigger problems than publically funded organisations. Our results offer some novel and relevant insights in the role and work of transition intermediaries and the development of community energy projects in times of crisis. These findings can help governments, intermediary organizations and citizen groups to design future transition processes in ways that are more resilient to external shocks.